2022
DOI: 10.1093/ntr/ntac023
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Tobacco Control Policies, and Persistent Smoking Among Older Adults: A Longitudinal Analysis of 11 European Countries

Abstract: Introduction Little is known about sociodemographic and macro-level predictors of persistent smoking when one has developed a health condition that is likely caused by smoking. We investigate the impact of gender, education, and tobacco control policies (TCPs) on persistent smoking among older Europeans. Methods Respondents (aged 50 +) with a smoking history and at least one smoking-related health condition were pooled from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A related study examined European countries. A related study examining persistent smoking behavior among older adults in European countries found that women, particularly those with low levels of education, were more likely to be persistent smokers [ 43 ]. The same results were obtained in Indonesia, where the overall upward trend was most pronounced, where the cohort RRs maintained a steady upward trend from 1910 to 1982 but showed a downward trend from 1985 to 1989, and where, as the world’s worst tobacco-using country, about 51.3% of adults and 66.2% of adolescents aged 13–15 years are regularly exposed to secondhand smoke [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A related study examined European countries. A related study examining persistent smoking behavior among older adults in European countries found that women, particularly those with low levels of education, were more likely to be persistent smokers [ 43 ]. The same results were obtained in Indonesia, where the overall upward trend was most pronounced, where the cohort RRs maintained a steady upward trend from 1910 to 1982 but showed a downward trend from 1985 to 1989, and where, as the world’s worst tobacco-using country, about 51.3% of adults and 66.2% of adolescents aged 13–15 years are regularly exposed to secondhand smoke [ 44 ].…”
Section: Discussionmentioning
confidence: 99%